2011
DOI: 10.5511/plantbiotechnology.10.1217a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular based evidence for a lack of gene-flow between Rosa×hybrida and wild Rosa species in Japan

Abstract: An important part of the assessment of the potential environmental impact from the introduction of a genetically modified (GM) plant is an evaluation of the potential for gene flow from the GM plant to related wild species. This information is needed as part of the risk-assessment process, in the context of whether gene flow to wild species is possible. One method for evaluating gene flow is to use molecular techniques to identify genes in wild species populations that may have originated from a cultivated spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…These results indicate that gene dispersal from the host and the two GM rose lines to R. multiflora, if any, is likely to be rare under natural condition. We previously showed that gene transfer from Rosaϫhybrida to Japanese wild roses could not be detected (Nakamura et al 2011). As the two GM rose lines used in this study are transgenic only in L1 cells, transgene flow from these GM rose lines to Japanese wild roses could not occur.…”
Section: Natural Crossingmentioning
confidence: 81%
See 2 more Smart Citations
“…These results indicate that gene dispersal from the host and the two GM rose lines to R. multiflora, if any, is likely to be rare under natural condition. We previously showed that gene transfer from Rosaϫhybrida to Japanese wild roses could not be detected (Nakamura et al 2011). As the two GM rose lines used in this study are transgenic only in L1 cells, transgene flow from these GM rose lines to Japanese wild roses could not occur.…”
Section: Natural Crossingmentioning
confidence: 81%
“…In a separate study, we extensively analyzed the seedlings of Japanese wild roses (R. multiflora, R. luciae and R. rugosa) growing in close proximity to Rosaϫhybrida and detected no gene flower from Rosaϫhybrida to the wild roses in the wild (Nakamura et al 2011). In that study, the KSN gene (a perpetual flowering gene found in cultivated rose but not Japanese wild roses) was used as a marker to detect whether there was any gene flow.…”
Section: Environmental Risk Assessment and Field Performance Of Rose mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, all cultivated roses are tetraploid, while all wild races that can cross-fertilize with the transgenic rose are diploid. Therefore, the resulting triploid progeny are infertile (Nakamura et al 2011a(Nakamura et al , 2011b. However, the evaluation of biodiversity impact in these plants consumed much time and incurred heavy costs.…”
Section: A Concept For Addressing the Biodiversity Impact Of Gm Flowersmentioning
confidence: 99%
“…In this issue, Suntory provide their technical data for the biodiversity impact evaluation of the blue rose (Nakamura et al 2011a(Nakamura et al , 2011b. Although this kind of work as well as the approaches to GMO production including isolation and characterization of applied genes as in this issue (Fukuchi-Mizutani et al 2011;Togami et al 2011) are sometimes difficult to publish as academic papers, we hope many scientific journals, including Plant Biotechnology will provide a place for the discussion of its importance as a part of academic research.…”
Section: A Concept For Addressing the Biodiversity Impact Of Gm Flowersmentioning
confidence: 99%